PERSEPSI GURU TERHADAP SISWA BERKESULITAN FUNGSIONAL DI SD NEGERI GUNUNG GATEP KABUPATEN LOMBOK TENGAH - Asri Fauzi; Ashar Pajarungi Anar; Aisa Nikmah Rahmatih; Ketut Sri Kusuma Wardani; Ni Luh Putu Nina Sri Warthini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
Inclusive education basically aims to facilitate the educational needs of children who experience physical, intellectual, social emotional disorders, learning difficulties, slow learning, motor disorders, and others. One of the schools that hold inclusive education in Central Lombok is Gunung Gatep Public Elementary School since 2012. The purpose of this study is to find out how class teachers' perceptions of students with functional difficulties in Gunung Gatep Public Elementary School. This type of research is a qualitative descriptive study, where researchers explain, analyze the facts found in the field. The subjects of this study were Gunung Gatep Elementary School teachers namely class 1, 2 and 3 teachers. Data collection techniques used by researchers were interviews, observation, and documentation. The results of this study indicate that teachers' perceptions of students who have functional difficulties are students with special characteristics that are different from students in general, students who have functional difficulties are students who need the same and appropriate Education services as other normal students. The class teacher's view of students with functional difficulties must be understood by those around them who not only see from their shortcomings but also from talent that must be cultivated with support and motivation from those around students who experience functional difficulties. Then from the results of the interview, the class teacher has increased knowledge about students with functional difficulties by attending workshops and training including: (1) training in the making of integrated lesson plans that include inclusive education in which the lesson plans have indicators, objectives, and learning steps for students with functional difficulties; (2) training in making and using media for children with functional difficulties, (3) training in learning methods and classroom settings so that students with functional difficulties can interact with other normal students